Treadmill test in hypothyroidism - Nigam, Pradeep; Baghel, P K (International Journal of Medical Research and Review, 2016)
Introduction: Thyroid hormone has a profound effect on a number of metabolic processes in virtually all tissues, with the heart being particularly sensitive to its effects. The hypothyroidism leads to increased body weight, hyperlipidemia and hypertension are the risk factors for coronary artery disease. Material and Methods: The hypothyroid patients were subjected to tread mill test and other required tests and results analyzed statistically. Results: tread mill test was positive in females more with history of previous risk factor for CAD and resting ECG changes with sedentary life style and tobacco addiction. Conclusion: Hypothyroidism is a definite risk factor for ischemic heart disease and exercise stress testing can help in early detection of occult coronary artery disease.